Maximal upper-body strength and oxygen uptake are associated with performance in high-level 200-m sprint kayakers. - Pickett, C. W.; Nosaka, K.; Zois, J.; Hopkins, W. G.; Blazevich, A. J. (The Journal of Strength and Conditioning Research, 2018)
Current training and monitoring methods in sprint kayaking are based on the premise that upper-body muscular strength and aerobic power are both important for performance, but limited evidence exists to support this premise in high-level athletes. Relationships between measures of strength, maximal oxygen uptake (VO2max), and 200-m race times in kayakers competing at national-to-international levels were examined. Data collected from Australian Canoeing training camps and competitions for 7 elite, 7 national, and 8 club-level male sprint kayakers were analyzed for relationships between maximal isoinertial strength (3 repetition maximum bench press, bench row, chin-up, and deadlift), VO2max on a kayak ergometer, and 200-m race time. Correlations between race time and bench press, bench row, chin-up, and VO2max were -0.80, -0.76, -0.73, -0.02, and 0.71, respectively (90% confidence limits ~±0.17). The multiple correlation coefficient for 200-m race time with bench press and VO2max was 0.84. Errors in prediction of 200-m race time in regression analyses were extremely large (~4%) in relation to the smallest important change of 0.3%. However, from the slopes of the regressions, the smallest important change could be achieved with a 1.4% (±0.5%) change in bench-press strength and a 0.9% (±0.5%) change in VO2max. Substantial relationships were found between upper-body strength or aerobic power and 200-m performances. These measures may not accurately predict individual performance times, but would be practicable for talent identification purposes. Training aimed at improving upper-body strength or aerobic power in lower performing athletes could also enhance the performance in 200-m kayak sprints.